Spatiotemporal hierarchy in antibody recognition against transmitted HIV-1 envelope glycoprotein during natural infection. Issue 1 (December 2016) - Jin, Su; Ji, Yangtao; Wang, Qian; Wang, Hua; Shi, Xuanling; Han, Xiaoxu; Zhou, Tongqing; Shang, Hong; Zhang, Linqi
Abstract Background Majority of HIV-1 infection is established by one transmitted/founder virus and understanding how the neutralizing antibodies develop against this virus is critical for our rational design an HIV-1 vaccine. Results We report here antibody profiling of sequential plasma samples against transmitted/founder HIV-1 envelope glycoprotein in an epidemiologically linked transmission pair using our previously reported antigen library approach. We have decomposed the antibody recognition into three major subdomains on the envelope and showed their development in vivo followed a spatiotemporal hierarchy: starting with the ectodomain of gp41 at membrane proximal region, then the V3C3V4 and the V1V2 of gp120 at the membrane distal region. While antibodies to these subdomains appeared to undergo avidity maturation, the early anti-gp41 antibodies failed to translate into detectable autologous neutralization. Instead, it was the much delayed anti-V3C3V4 and anti-V1V2 antibodies constituted the major neutralizing activities. Conclusions Our results indicate that the initial antibody response was severely misguided by the transmitted/founder virus and future vaccine design would need to avoid the ectodomain of gp41 and focus on the neutralizing targets in the V3C3V4 and V1V2 subdomains of gp120.